CIRCULATION OF INFLUENZA VIRUSES AMONG HUMANS AND SWINE IN THE TERRITORY OF KAZAKHSTAN DURING 2017–2018 - Klivleyeva N.G.; Ongarbayeva N.S.; Saktaganov N.T.; Glebova T.I.; Lukmanova G.V.; Sayatov M.Kh.; Berezin V.E.; Nusupbaeva G.E.; Aikimbayev A.M.; Webby R.J. (Scientific Journal of Pedagogy and Economics, 2019)
251 biosamples (191 nasopharyngeal swabs and 60 blood serums) were obtained from humans at healthcare institutions located in various regions of the Republic of Kazakhstan. 369 biosamples (330 nasopharyngeal swabs and 39 blood serums) were collected from swine farms. In the polymerase chain reaction performed on 191 samples collected from humans, the genetic material of influenza A virus was detected in 14.14% of cases, that of influenza B virus in 5.24%. When carrying out subtyping, influenza A/H1N1 virus RNA was identified in 4.71% of samples, A/H3N2 virus RNA in 4.19%. In 330 samples obtained from swine, the genetic material of influenza virus was found in 3.33% of cases, of which influenza A/H1N1 virus RNA was detected in 2.12%, and A/H3N2 virus RNA in 1.21%. The results obtained in the polymerase chain reaction, as well as data from serological studies in the hemagglutination inhibition assay and enzyme immunoassay, indicate co-circulation of influenza A/H1N1 and A/H3N2 and B viruses among humans and influenza A/H1N1 and A/H3N2 viruses among swine in various regions of Kazakhstan during 2017-2018. When carrying out virological study of biosamples collected from humans and swine, 10 hemagglutinating agents were isolated in chicken embryos and identified as influenza viruses with antigenic formulae A/H1N1, A/H3N2, and B. The results of virological and serological studies underline the importance of conducting continuous monitoring of the circulation of influenza viruses among humans and swine in Kazakhstan to identify the possibility of interspecies transmission of the infectious agent.